A document analysis for improving Oral Health Services in Niue - Nosa, Vili; Pili , Nafanua; Tatui , Leroy (Advances in Social Sciences Research Journal, 2021)
ABSTRACT Background There is very little research that focuses on oral health in the Pacific region. This paper outlines a document analysis of dental reports from the dental clinic in Niue and to examine their oral health and dental services. Furthermore this paper is intended to highlight how oral services in Niue can be improved for better oral health care for the Niue community. Methods: A document analysis of seven Niue dental reports between July 2011 to July 2018. The information found in the documents were organised under the sections clinical data reporting. The analysis also focused on a strength based approached for discussing the key challenges; the main achievements; and future recommendations for improving dental services for Niue. Results: Dental caries are the most common reason for tooth extractions followed by periodontal diseases. Primary school students are affected the most with 60 percent of students experiencing untreated dental caries. Among high school students, the rate of dental caries experienced is relatively low. Women appear to attend the dental clinic more than men however the number of visits for both men and women has declined. The key challenges faced by the dental team were a lack of resources specifically shortage of computers and functioning dental chairs, unfamiliarity with MEDTECH and limited staff development opportunities. Despite these challenges, the team were still able to establish the ‘Atuhau Mamali’ programme and upskill one staff member through professional development. Other achievements included reducing noise pollution, allocating a budget for safety equipment and establishing clinical guidelines for practice. Conclusions: Recommendations to improve oral health and dental services in Niue are to deliver targeted dental caries interventions in schools, introduce stronger food policies and to implement collaborative networks across the Pacific region. It is recommended that the Niue dental team develop more rigorous methods of data documentation to gain a more accurate picture of oral health in the country.